The effect of short-term isokinetic training on force and rate of velocity development - Brown, L. E.; Whitehurst, M. (The Journal of Strength and Conditioning Research, 2003)
This study determines the effects of short-term isokinetic training on rate of velocity development (RVD) and force. Three groups were pre- and posttested for knee extension RVD and force at 1.04 (slow) and 4.18 rad/s (fast) on a Kin-Com dynamometer. The slow and fast groups completed 2 days of velocity-specific training, whereas the control group did not train. Four-way analysis of variance results demonstrated significant (p < 0.05) decreases in RVD between pre- and posttests for the slow group at the slow velocity (RVD-1.25 ± 0.04° vs. 1.08 ± 0.03°) and for the fast group at the fast velocity (RVD-14.24 ± 0.33° vs. 13.59 ± 0.29°). Force exhibited no significant differences between testing days for any group. These results demonstrate that short-term isokinetic training results in velocity-specific RVD improvements. These acute RVD improvements may serve to offset strength deficits in power environments on the basis of the mutable relationship between force and velocity.